Study on Extraction Process of Curcuma zedoaria Volatile Oil and Its Effect on Anticancer - Guo, Shan-Bin; Tian, Yue; Jian, Ling-Yan (Asian Journal of Chemistry, 2013)
To investigate the extraction process of Curcuma zedoaria volatile oil and its effect on proliferation and apoptosis of human gastric cancer SGC-7901 cells. Orthogonal experimental method was used to analyze the effect of extraction factors-crushing degree, amount of added water and distillation time-on Curcuma zedoaria oil; MTT assay, PI staining and flow cytometry were used to study the effect of Curcuma zedoaria oil on human gastric cancer SGC-7901 cells. The crushing degree, amount of added water and distillation time all affect the extraction of Curcuma zedoaria oil, Curcuma zedoaria oil can inhibit human gastric cancer SGC-7901 cell proliferation and induce its apoptosis.